2-Oxo-Imidazole-Containing Dipeptides Play a Key Role in the Antioxidant Capacity of Imidazole-Containing Dipeptides - Shingo Kasamatsu; Somei Komae; Kana Matsukura; Yuki Kakihana; Koji Uchida; Hideshi Ihara (MDPI AG, 2021)
There is substantial evidence for the antioxidant functions of imidazole-containing dipeptides (IDPs), including carnosine and anserine, under physiological and pathological conditions in vivo. However, the detailed mechanism underlying the antioxidant functions is still poorly understood. Recently, we discovered the endogenous production of 2-oxo-imidazole-containing dipeptides (2-oxo-IDPs), such as 2-oxo-carnosine and 2-oxo-anserine, as novel derivatives of IDPs in mouse tissues and revealed that the antioxidant capacity of 2-oxo-carnosine was much greater than that of carnosine. However, the antioxidant capacity of 2-oxo-IDPs still remains unclear. In this study, we evaluated 2-oxo-carnosine and 2-oxo-anserine by multiple in vitro assays, such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, ferric reducing/antioxidant power, and oxygen radical absorbance capacity assays in comparison with the corresponding IDPs, carnosine and anserine. All the assays employed herein demonstrated that 2-oxo-carnosine and 2-oxo-anserine exhibited a greater antioxidant capacity than that of the corresponding IDPs. Quantitative high-performance liquid chromatography tandem mass spectrometry revealed that commercial IDPs standards were contaminated with a certain amount of 2-oxo-IDPs, which was correlated with the antioxidant capacity. DPPH radical scavenging assay revealed that the elimination of contaminated 2-oxo-IDPs from the IDPs standards caused a significant decrease in the antioxidant capacity compared to the original IDPs standards. These results suggest that the main driver of the antioxidant capacity of IDPs is 2-oxo-IDPs; accordingly, the conversion of IDPs to 2-oxo-IDPs may be a critical step in the antioxidant functions.